2022
DOI: 10.1088/1741-2552/ac889f
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial ultrasound neuromodulation induces neuronal correlation change in the rat somatosensory cortex

Abstract: Transcranial focused ultrasound (tFUS) is a neuromodulation technique which has been the focus of increasing interest for noninvasive brain stimulation with high spatial specificity. Its ability to excite and inhibit neural circuits as well as to modulate perception and behavior has been demonstrated, however, we currently lack understanding of how tFUS modulates the ways neurons interact with each other. This understanding would help elucidate tFUS’s mechanism of systemic neuromodulation and allow future deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Recent research has indicated that TUS monotherapy can enhance synaptic rehabilitation at 250-720 I SPTA (mW/cm 2 ) [33][34][35][36]; the I SPTA used was 5 to 14 times higher than the 53 mW/cm 2 we utilized. Additionally, the combination of ultrasound with microbubbles to invasively open the blood-brain barrier also enhances synaptic rehabilitation [37][38][39].…”
Section: Discussionmentioning
confidence: 82%
“…Recent research has indicated that TUS monotherapy can enhance synaptic rehabilitation at 250-720 I SPTA (mW/cm 2 ) [33][34][35][36]; the I SPTA used was 5 to 14 times higher than the 53 mW/cm 2 we utilized. Additionally, the combination of ultrasound with microbubbles to invasively open the blood-brain barrier also enhances synaptic rehabilitation [37][38][39].…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown that different types of neurons from Layer 5 and Layer 6 are more strongly connected to the thalamus, especially POm. And previous study showed that tFUS has different effects on neurons in different layers of cortex [55]. Further studies are warranted, specifically recording from broader layers and using neuronal subtype labelling methods (such as optogenetic technique) to investigate the specifics of these responses.…”
Section: Discussionmentioning
confidence: 99%
“…While thin ring transducers have been applied in mouse imaging studies 34,50 , their focusing ability is even more limited than standard focused ultrasound transducers. Similarly, collimators have been used to further limit the sonication area [51][52][53] (Fig. 2e) but are too bulky for optical imaging compatibility.…”
Section: Calcium Imaging Analysis Of Ultrasound Stimulation Effect On...mentioning
confidence: 99%